2004
DOI: 10.1002/ceat.200407033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mass Transfer on the Production of Biodiesel

Abstract: The growing interest in alternative fuels makes it important to optimize classical routes for the production of biodiesel, as well as to explore and introduce non‐classical alternatives. For the investigations reported in this article, a two‐phase system consisting of rape oil and methanol was chosen. The goal of the experiments was to investigate whether ultrasound had a significant influence on the conversion rate of the reaction and the reaction mechanism, or if more intensive mixing of the reaction mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Lifka and Ondruschka [37] reported that agitation is an important factor for biodiesel production. Therefore, in this study, the agitation speed was investigated to improve the FAME yield from dried biomass.…”
Section: Effect Of the Agitation Speed On The Fame Yield From Dried Bmentioning
confidence: 99%
“…Lifka and Ondruschka [37] reported that agitation is an important factor for biodiesel production. Therefore, in this study, the agitation speed was investigated to improve the FAME yield from dried biomass.…”
Section: Effect Of the Agitation Speed On The Fame Yield From Dried Bmentioning
confidence: 99%
“…Figure 4 shows the pseudo second-order reaction with respect to TAG for commercial, corn and grape seed oils during the whole reaction period and only in the initial period of the reaction for canola and palm oils. It appears that base-catalyzed methanolysis of vegetable oils with high percentage of linoleic acid follows the second-order reaction kinetics such as for the commercial, corn, grape seed (52.5, 66.5 and 82.2%, respectively) [6] sunflower (68.7%) [11], cottonseed (57.4%) [10] and soybean (typically 55.5%) [22,32] oils. It appears that base-catalyzed methanolysis of vegetable oils with high percentage of linoleic acid follows the second-order reaction kinetics such as for the commercial, corn, grape seed (52.5, 66.5 and 82.2%, respectively) [6] sunflower (68.7%) [11], cottonseed (57.4%) [10] and soybean (typically 55.5%) [22,32] oils.…”
Section: Reaction Kinetic Modelmentioning
confidence: 99%
“…Methanol and TAG are immiscible [2] and the reaction between the reactants occurs on the interfacial surface [3]. Based on the known effects of ultrasonic cavitation such as mixing, heating and disruption of the interface, some researchers have sped up the reaction rate by carrying out methanolysis in the presence of ultrasound [5][6][7][8][9][10][11][12]. Based on the known effects of ultrasonic cavitation such as mixing, heating and disruption of the interface, some researchers have sped up the reaction rate by carrying out methanolysis in the presence of ultrasound [5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…As mentioned previously, high concentrations of alkaline catalyst form soaps in the presence of large residues of fatty acids resulting in emulsion formation between soaps and water molecules, thus leading to low yields of methyl esters. Lifka and Ondruscka [31] studied the effect of ultrasonication versus mechanical stirring on the alkaline transesterification of rapeseed using NaOH at a concentration of 0.5% w/w at 45 °C and reported a conversion of 80-85% obtained for both the ultrasonicated and mechanically stirred reactions after 30 mins. Georgogianni et al [32] also reported a yield of 81% with regards to using a catalyst concentration of 1.5% w/w NaOH on sunflower seed oil which slightly corresponds to the value reported above in Table 2.…”
Section: Effect Of Catalyst Concentrationmentioning
confidence: 99%